Segmental bioelectrical impedance analysis for Korean older population with cold pattern - Doan, Dieu Ni Thi; Kim, Kahye; Kim, Seul Gee; Lee, Siwoo; Lee, Kun Ho; Kim, Jaeuk (Frontiers in Nutrition, 2022)
This study examined the association of whole-body composition and segmental bioimpedance variables with cold patterns (CP) in different sexes. We assigned 667 older individuals to a CP group (n=488) and a non-CP group (n=179) by using an eight-item self-administered questionnaire. Seven body composition variables and three pairs of segmental bioimpedance variables for the upper and lower extremities, which were obtained from a segmental multifrequency bioimpedance analyzer, were employed to investigate their association with CP. Participants’ characteristics were first described. Then we compared the selected body composition and bioimpedance variables between the CP and non-CP groups. Finally, their association with CP was investigated using univariate and multivariate regression analyses. All analyses were performed separately for women and men. As a result, both women and men exhibited a comparable mean age in the CP and non-CP groups; however, women with CP had significantly lower blood pressures, whereas men with CP showed a higher proportion of osteoarthritis than those without CP. Compared with the non-CP group, individuals with CP exhibited significantly smaller body sizes indicated by shorter height and smaller weight, lower body mass index, and smaller volume-to-body surface area ratio in both sexes. After controlling for age, height, weight, and other covariates, we found significant reductions in body lean mass such as fat-free mass and body cell mass, basal metabolic rate per unit mass, total body water, and intra-to-extracellular water ratio in the CP group. With regard to segmental bioimpedance analysis, the resistance ratios and phase angles in the upper and lower extremities yield significant associations with CP incidence, as demonstrated by the odds ratio (95% confidence interval) of 1.72 (1.16–2.57), 1.69 (1.18–2.48), 0.60 (0.40–0.89), and 0.57 (0.39–0.82), respectively. However, these results did not emerge in men. In conclusion, abnormal cellular water distribution and deterioration in body cell mass and/or cell strength are associated with CP prevalence, regardless of age, height, weight. These findings are similar in the upper and lower extremities and are more pronounced in women. The abovementioned patterns may be considered effective indicators for identifying CP in the older adult population.